2016
DOI: 10.3389/fncel.2016.00117
|View full text |Cite
|
Sign up to set email alerts
|

Soluble RAGE Treatment Delays Progression of Amyotrophic Lateral Sclerosis in SOD1 Mice

Abstract: The etiology of amyotrophic lateral sclerosis (ALS), a fatal motor neuron disorder characterized by progressive muscle weakness and spasticity, remains largely unknown. Approximately 5–10% of cases are familial, and of those, 15–20% are associated with mutations in the gene encoding Cu/Zn superoxide dismutase (SOD1). Mutations of the SOD1 gene interrupt cellular homeostasis and contribute to cellular toxicity evoked by the presence of altered SOD1, along with other toxic species, such as advanced glycation end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 56 publications
3
47
0
Order By: Relevance
“…Importantly, sRAGE treatment not only reduced motor neuron death but also decreased astrogliosis, indicating a more homeostatic profile in multiple cell types [99]. Altogether, a burgeoning body of literature suggests that RAGE activation, driven by an increased availability of ligands, is likely a contributing factor to ALS pathology.…”
Section: Amyotrophic Lateral Sclerosis Another Inflammatory Syndromementioning
confidence: 94%
See 2 more Smart Citations
“…Importantly, sRAGE treatment not only reduced motor neuron death but also decreased astrogliosis, indicating a more homeostatic profile in multiple cell types [99]. Altogether, a burgeoning body of literature suggests that RAGE activation, driven by an increased availability of ligands, is likely a contributing factor to ALS pathology.…”
Section: Amyotrophic Lateral Sclerosis Another Inflammatory Syndromementioning
confidence: 94%
“…Furthermore, this increase of RAGE and its ligands was recapitulated in one of the most commonly employed ALS rodent models, murine lines containing the familial G93A mutation in superoxide dismutase 1 (SOD1), as discovered in human ALS populations [3,99,100]. In these models, nerve growth factor (NGF) is post-translationally modified by oxidation and contributes to RAGE signaling-induced motor neuron death when normal motor neurons are co-cultured with SOD1 G93A astrocytes [101].…”
Section: Amyotrophic Lateral Sclerosis Another Inflammatory Syndromementioning
confidence: 97%
See 1 more Smart Citation
“…In a recent study, Juranek and colleagues showed that administration of the soluble form of RAGE, sRAGE, to SOD1 G93A mice significantly prolonged life span and delayed disease progression compared to vehicle treatment [32]. At the end stage of disease, spinal cord tissue revealed higher numbers of neurons and less astrogliosis in the sRAGE-treated group vs. the mice receiving vehicle.…”
Section: 0 Studies In Animal Modelsmentioning
confidence: 99%
“…Multiple studies have demonstrated that RAGE and its inflammatory ligands AGE, S100β and HMGB1 are up-regulated in the spinal cord of human ALS patients compared to healthy controls [6,11]. Prior studies have also demonstrated that inhibition of RAGE using soluble RAGE form has beneficial effects on survival and disease progression in animal models of ALS [10,12], suggesting RAGE could play a pathogenic role in the disease. Although these studies have indicated detrimental actions of RAGE activation in ALS pathogenesis, the specific molecular mechanism by which RAGE contributes to neurodegeneration remains unknown.…”
Section: Introductionmentioning
confidence: 99%